The 1970s Portrait of a Generation at the Doorstep - Nugin, Raili (Politics and Society in the Baltic Sea Region, 2015)
This book draws a sociological portrait of the age group born in the 1970s in Estonia and discusses its generational features and constructions. This cohort's coming of age coincided with the social and emotional turmoil of the re-independence movement in the late 1980s and with the transformation of society in the 1990s. This was the first cohort to negotiate its transition to adulthood in the new society, starting some new patterns of socialization, while also sharing some practices and experiences with older cohorts. Based on qualitative interviews as well as an analysis of media discourses and statistical data, the book traces the emergence of a new generation that draws its very own lessons from the past and from the social transformations that influenced life courses and careers. The book provides an intriguing discussion of socialization patterns and generation formation against the backdrop of post-socialist transformation. In addition, it provides a fascinating insight into the mind-set and experiences of a generation in the making, already shaping today's society and culture.